A high performance photothermal film with spherical shell-type metallic nanocomposites for solar thermoelectric conversion. Issue 17 (14th April 2015) - Kosuga, Atsuko; Yamamoto, Yasuyuki; Miyai, Moe; Matsuzawa, Mie; Nishimura, Yushi; Hidaka, Shimpei; Yamamoto, Kohei; Tanaka, Shin; Yamamoto, Yojiro; Tokonami, Shiho; Iida, Takuya
Abstract : A photothermal film (PTF) consisting of densely assembled gold nanoparticle-fixed beads (AuNP-FBs) on a low cost polymer substrate is successfully fabricated. Abstract : A photothermal film (PTF) with densely assembled gold nanoparticle-fixed beads on a polymer substrate is fabricated. Remarkably, a temperature rise higher than 40 °C is achieved in the PTF with only 100 seconds of artificial solar irradiation, and the output power of the thermoelectric device was enhanced to be one order higher than that without PTF. These results will pioneer a rapid solar thermoelectric device.